Characterization of the Guinea Pig Production Chain in Southern Colombia and Identification of Determining Factors for Adequate Provision of Extension Services - Forero, Oscar A.; Patiño, Rocio E.; Carlosama, Luz Dary; Portillo, Paola A. (Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2024)
The development of agrifood systems in Latin America reflects contrasting policy goals. Most governments advocate that “modernization,” measured as increased rates of technology adoption, is the way to address persistent food insecurity. By contrast, peasants’ and indigenous people’s organizations and social movements propose advancing knowledge co-production and co-innovation to increase the resilience of agrifood systems. Colombia reformed the National Innovation System for Agriculture in 2017. The policy reform instructed transitioning from providing “technical advice” to rural extension services. The research aimed to fill the knowledge gap regarding the transition to rural extension along the guinea pig production chain. In addition to characterizing the production chain, we conducted qualitative and reflectivity analyses to understand better how institutional practices and research cultures hinder or promote transitioning to rural extension. The investigation revealed that small-scale farmers who rely on the production and commercialization of guinea pigs as a livelihood strategy have continued receiving advice to adopt the latest technologies. In closing, besides addressing technological deficits or inefficiencies, a systemic approach that considers cultural context and identity must integrate into rural extension to ensure technological adoption is aligned with the sustainability and resilience objectives of the guinea pig production chain.